Extract of Ganoderma sinensis spores induces cell cycle arrest of hepatoma cell via endoplasmic reticulum stress. (1st January 2021) - Lin, Weiming; Gu, Li; Zhu, Ling-Yan; Zhou, Sha; Lian, Danhong; Xu, Yongquan; Zheng, Limin; Liu, Xin; Li, Lian
Abstract: Context: Ganoderma sinensis Zhao, Xu et Zhang (Ganodermataceae) has been used for the prevention or treatment of a variety of diseases, including cancer. Objective: We investigated the antitumor activity and mechanism of an extract from G. sinensis against hepatocellular carcinoma. Materials and methods: A G. sinensis extract (GSE) was obtained from sporoderm-broken G. sinensis spores by supercritical fluid carbon dioxide extraction. Hepatoma cells, HepG2 cells, were treated with emulsified sample of GSE at 12.5, 25, 50, 100 and 150 μg/mL for 24 h. The Alamar Blue assay was used to examine growth inhibitory effects. Changes in cell structure and morphology were assessed via transmission electron microscopy and confocal laser scanning microscope. Cell cycle distribution was analysed by flow cytometry. Results: GSE suppressed the proliferation of HepG2 cells (IC50 =70.14 μg/mL). Extensive cytoplasmic vacuolation originating from dilation of the endoplasmic reticulum (ER) was shown in GSE-treated HepG2 cells. GSE treatment also upregulated the expression of ER stress-related proteins in HepG2 cells. Cells tended to be arrested at the G2/M cell cycle stage after GSE treatment (30.8 ± 1.4% and 42.2 ± 2.6% at GSE with 50 μg/mL and 100 μg/mL vs. 21.03 ± 1.10%, control). Pre-treatment with salubrinal, an inhibitor of ER stress, effectively attenuated cell cycle arrest induced by GSE. Discussion and conclusions: Our findings provide new evidence that GSE suppresses growth of cancer cells in vitro through activating the ER stress pathway. The GSE may be clinically applied in the prevention and/or treatment of cancer.